2013
DOI: 10.1176/appi.ps.003382012
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early Readmission to Acute Care for Persons With Schizophrenia Taking Antipsychotic Medications

Abstract: OBJECTIVE The study examined risk factors for readmission to acute care among Florida Medicaid enrollees with schizophrenia treated with antipsychotics. METHODS Medicaid and service use data for 2004 to 2008 were used to identify adults with schizophrenia discharged from hospitals and crisis units who were taking antipsychotics. Data were extracted on demographic characteristics, service use before admission, psychopharmacologic treatment after discharge, and readmission to acute behavioral health care. Cox pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
1
39
2
Order By: Relevance
“…The mean age of the sample was 44.33 years, which is in agreement to other studies which presented mean higher than 37 years of age 7,11,16,20,21,24,33,34 . The findings of the present study did not show association between age and frequent readmissions, results corroborated by some studies in the area 24,33,34 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean age of the sample was 44.33 years, which is in agreement to other studies which presented mean higher than 37 years of age 7,11,16,20,21,24,33,34 . The findings of the present study did not show association between age and frequent readmissions, results corroborated by some studies in the area 24,33,34 .…”
Section: Discussionsupporting
confidence: 91%
“…This duration is even higher when compared to other studies evaluating this variable. Another study carried out in São Paulo 25 found a mean of 17.3 days and, in international ones, a mean duration between 10 and 20 days of hospitalization 6,7,11,16,21,34 . Finally, considering the variables of NPC follow-up, we highlight the data of 34.4% of participants in the study who did not follow-up before the investigated hospitalization, as well as over half the users in first hospitalization, which shows this ends up being the gateway for mental health care access.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although studies in U.S. settings have had mixed findings (2), studies in other industrialized countries have shown that stays of less than eight days are associated with higher-than-average 30-day readmission rates, whereas stays between 25 and 30 days are not (13,14). Furthermore, a recent U.S. study showed that shorter hospitalizations lead to higher 30-day readmission rates (15). Evidence also suggests that the financial costs of longer hospitalizations are largely offset by lower readmission and emergency room utilization rates, not to mention less tangible benefits such as greater satisfaction with care, treatment retention, and improved quality of life (16).…”
Section: Discussionmentioning
confidence: 99%
“…Several patient-related factors are associated with readmission risk, including poor medication adherence (1); substance use disorders (1); a diagnosis of schizophrenia, bipolar disorder, or depression (4); and comorbid medical disorders (5). Homelessness or residence in an institutional setting are social factors associated with psychiatric readmission (2), and previous hospitalizations (6), length of hospital stay (7,8), and lack of adequate postdischarge care for psychiatric and substance use disorders are system-related factors (9).…”
mentioning
confidence: 99%